Effect of Radiofrequency Thermal Ablation Treatment on Nasal Ciliary Motility: A Study with Phase‐Contrast Microscopy. (9th February 2016) - Rosato, Chiara; Pagliuca, Giulio; Martellucci, Salvatore; de Vincentiis, Marco; Greco, Antonio; Fusconi, Massimo; De Virgilio, Armando; Gallipoli, Camilla; Simonelli, Marilia; Gallo, Andrea
Abstract : Objective: To investigate the efficacy of nasal ciliary motility after radiofrequency ablation treatment in patients with isolated inferior turbinate hypertrophy and to clarify how long until normal ciliary function is restored. Study Design: Prospective, single‐group, pretest‐posttest design. Setting: Academic tertiary care medical center. Subjects and Methods: This study involved 34 adult patients affected by nasal obstruction due to inferior turbinate hypertrophy who underwent radiofrequency ablation treatment between June and December 2014. Diagnosis was assessed according to clinical history, nasal endoscopy, and active anterior rhinomanometry. Cytologic samples were collected by nasal scraping before surgery and 1, 2, and 3 months after surgery. Ciliary motility was evaluated by nasal cytology with phase‐contrast microscopy. Functional aspects of nasal mucosa were studied, with a focus on 3 parameters: (1) nasal mucociliary clearance, assessed by saccharin nasal transit time test; (2) percentage of ciliated cell motility, measured as the ratio between cells with motility and cells without motility; and (3) efficacy of ciliary motility, measured as the ratio between cells with valid motility and cells with hypovalid motility. Results: Ciliary motility and ciliary efficacy showed a significant reduction after 1 and 2 months from surgery, returning to normal values within 3 months. No significant changes in saccharin nasal transit time were recorded during the follow‐up. Conclusions: The outcomes of this study suggest that radiofrequency ablation treatment causes ciliary motility changes of nasal mucosa that are completely restored after at least 3 months after surgery. These cytologic abnormalities do not affect nasal functionality.